Financial Transactions Tax : Panacea, Threat, or Damp Squib? - Honohan, Patrick; Yoder, Sean (2012)
Attempts to raise a significant percentage of gross domestic product in revenue from a broad-based financial transactions tax are likely to fail both by raising much less revenue than expected and by generating far-reaching changes in economic behavior. Although the side-effects would include a sizable restructuring of financial sector activity, this would not occur in ways corrective of the particular forms of financial overtrading that were most conspicuous in contributing to the crisis.